Competitiveness of the Russian space industry in the global space services market - A. В. Khodykin (Вестник университета)
The article carries out an analysis of the competitiveness of the Russian space industry in the international space services market according to the following indicators: the volume of budget of national space organizations, the volume of the commercial space exploration market, the number of space launches, positions in manned cosmonautics, production of spacecrafts, deep space exploration, staffing of the space industry and international integration in the space sphere. The paper conducts a SWOT-analysis of the Russian space industry. Its main strengths are: leading positions in manned cosmonautics, leading positions in the number of space launches per year, and extensive experience in space exploration. The greatest concern is caused by: the lack of development of space robotics, insufficient programs for the development of deep space, financial problems and the private sector of Russian cosmonautics, which is in its infancy. The author substantiates the necessity of reforming the Russian space industry.